Settlement Comparison Research in Response to Gravel Columns with Concrete under a Distributed Vertical Dynamic Load - Cardenas, V. (2022)
Currently there are different techniques of soil improvement. One of them is the gravel columns that is one of the most popular and profitable techniques for soil improvement. This method of breeding increases the physical and mechanical properties of the soils. However, it has limitations, because part of the aggregates in non-specific areas can generate settlement that affects the structure. In this study, it reduces the settlement of the gravel column by making a change in a certain percentage in its structure by a concrete that is not reinforced. Different heights of the concrete are visualized, in addition to having different variants such as columns that are next to the base, as well as the columns that are on the sandy ground. The research was carried out with the simple compression machine with the concept of unit cell. The yield of the hybrid columns (gravel and concrete) had a better yield which was 20% compared to the traditional gravel columns.